2023
DOI: 10.21873/anticanres.16241
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Recombination Defects and Mutations in DNA Damage Response (DDR) Genes BesidesBRCA1andBRCA2as Breast Cancer Biomarkers for PARP Inhibitors and Other DDR Targeting Therapies

Abstract: Homologous recombination repair (HRR) is the cellular mechanism for error-free repair of double strand DNA (dsDNA) breaks. Cancer cells with mutations in both alleles of genes encoding for proteins involved in HRR, such as BRCA1 and BRCA2, have defects in the repair process. As a result, these cells repair dsDNA breaks with alternative mechanisms, such as non-homologous end joining. In breast cancers with germline mutations in BRCA1 and BRCA2 genes, HRR defects result in sensitivity to PARP inhibitors, drugs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…With this information, researchers can choose suitable ILC/ILC-like cell lines based on the deregulated pathway on interest. Notably, each of these pathways is druggable using systematic or targeted agents e.g., endocrine therapies to against hormone signaling, HER2 and PI3K inhibitors against RTK signaling 98,99 , chemotherapy and CDK4/6 inhibitors 54 for inhibiting cell cycle and proliferation and PARP inhibitors against tumors with homologous repair defects (HRD) 100 . Knowledge of these deregulated pathways in ILC/ILC-like cell lines will be critical for developing precision therapies for human-ILC disease.…”
Section: Resultsmentioning
confidence: 99%
“…With this information, researchers can choose suitable ILC/ILC-like cell lines based on the deregulated pathway on interest. Notably, each of these pathways is druggable using systematic or targeted agents e.g., endocrine therapies to against hormone signaling, HER2 and PI3K inhibitors against RTK signaling 98,99 , chemotherapy and CDK4/6 inhibitors 54 for inhibiting cell cycle and proliferation and PARP inhibitors against tumors with homologous repair defects (HRD) 100 . Knowledge of these deregulated pathways in ILC/ILC-like cell lines will be critical for developing precision therapies for human-ILC disease.…”
Section: Resultsmentioning
confidence: 99%
“…This comprehensive analysis specifically examined mutations in genes related to HRR genes, excluding BRCA1/2 from consideration. This analysis demonstrated that the occurrence of mutations in HRR genes remained relatively infrequent, comprising less than 1% of cases, with ATM (5.2%), CHEK2 (1.6%), and PALB2 (0.9%) exhibiting the highest prevalence rates [24].…”
Section: Hrr-related Mutationsmentioning
confidence: 89%
“…Nevertheless, increasing evidence has shown that PARPi resistance is still present in patients without BRCA1/2 mutations; thus, massive efforts have been made to investigate other potential markers for predicting the sensitivity of PARPis. Among these genes, those involved in HR pathways, such as RAD51, ATM and ATR, are the most explored candidates [ 39 , 40 ]. Preclinical studies have shown that the expression of these genes is positively correlated with sensitivity to PARPi treatment and can enhance the response to PARPi treatment in cancer cells.…”
Section: Discussionmentioning
confidence: 99%